2006
DOI: 10.1016/j.ejcnurse.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Patients: Choice in Cardiac Rehabilitation

Abstract: Understanding the factors that influence patient's choices may help professionals guide them to the most appropriate CR method and hence improve uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 25 publications
3
82
0
Order By: Relevance
“…This finding is supported by others who have reported that patients learning needs vary according to their stage of recovery [31][32][33] and that the optimum time for realistic learning is during early convalescence [33]. The rapid throughput of patients and emotional shock experienced by them meant that the ability to absorb information during hospitalisation is somewhat limited.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This finding is supported by others who have reported that patients learning needs vary according to their stage of recovery [31][32][33] and that the optimum time for realistic learning is during early convalescence [33]. The rapid throughput of patients and emotional shock experienced by them meant that the ability to absorb information during hospitalisation is somewhat limited.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies have shown similarly varied responses [25,[32][33]. The fact that cardiac patients are not always aware of who might be best placed to provide them with health information [33] may explain these results. In addition participants' preferences were influenced by their underlying beliefs and expectations of practitioners' roles.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other than distance/travel time and rurality status, the following barriers were often self-reported: heavy traffic (Stokes 2008), parking problems, inconvenient program locations (Grace et al 2002), cost of traveling, not having a driver's license or inability to drive (Dunlay et al 2009, Winberg 2002, Jones et al 2007, Dalal, Evans 2003, Wingham et al 2006, and inclement weather leading to hazardous or congested traffic conditions (Blanchard et al 2003, Fleury et al 2004). Indeed, for rural patients, factors other than proximity to a program may influence attendance, such as the quality of roads and harsh weather in particular for northern-residing outpatients (Curnier, Savage & Ades 2005, Pell, Morrison 1998).…”
Section: Other Geographic Barriers To Cr Utilizationmentioning
confidence: 99%
“…50,51 They noted that patients benefited from group camaraderie and the opportunity to compare their progress with that of others, as has been found in other studies. 52,53 Patients may tend to view cardiac rehabilitation as being predominantly about exercise, 50,54 but other components of cardiac rehabilitation perceived as important by patients include advice, reassurance, and psychological support. [55][56][57] However, a number of barriers to patients attending cardiac rehabilitation have been found, of which transport difficulties are a commonly cited barrier.…”
Section: Patient Perspectives On Cardiac Rehabilitation Programsmentioning
confidence: 99%